2015
DOI: 10.1128/jcm.03002-14
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Peptide Arrays for Detection of Specific Anti-Hepatitis D Virus (HDV) Genotype 1, 6, and 8 Antibodies among HDV-Infected Patients by Surface Plasmon Resonance Imaging

Abstract: iLiver diseases linked to hepatitis B-hepatitis D virus co-or superinfections are more severe than those during hepatitis B virus (HBV) monoinfection. The diagnosis of hepatitis D virus (HDV) infection therefore remains crucial in monitoring patients but is often overlooked. To integrate HDV markers into high-throughput viral hepatitis diagnostics, we studied the binding of anti-HDV antibodies (Abs) using surface plasmon resonance imaging (SPRi). We focused on the ubiquitous HDV genotype 1 (HDV1) and the more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
5
0
2
Order By: Relevance
“…Interestingly, the binding affinity of PGLI-M3 to serum antibodies measured by SPR was almost 30-fold lower than that measured by a solution binding assay (ELISA), in which the SPR technology was able to detect antibodies with just as few as 0.03 µg of the peptide, while ELISA required 1 µg per reaction. It is important to note that the versatility of the SPR platform has allowed not only the evaluation of peptide ligands to mycobacteria (Ngubane et al, 2013), but also has been used as immunosensors for hepatitis (Villiers et al, 2015) or for detection of salivary proteins (Musso et al, 2015), and also for characterization of binding affinity of human proteins to M. leprae glycoproteins (Kim et al, 2015). Another advantage of this platform is the possibility to transform angular variations in absolute values, which present greater application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the binding affinity of PGLI-M3 to serum antibodies measured by SPR was almost 30-fold lower than that measured by a solution binding assay (ELISA), in which the SPR technology was able to detect antibodies with just as few as 0.03 µg of the peptide, while ELISA required 1 µg per reaction. It is important to note that the versatility of the SPR platform has allowed not only the evaluation of peptide ligands to mycobacteria (Ngubane et al, 2013), but also has been used as immunosensors for hepatitis (Villiers et al, 2015) or for detection of salivary proteins (Musso et al, 2015), and also for characterization of binding affinity of human proteins to M. leprae glycoproteins (Kim et al, 2015). Another advantage of this platform is the possibility to transform angular variations in absolute values, which present greater application in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Enander et al (2008) This clinical potential was also demonstrated by Villiers et al (2015). This group projected a protein/peptide array to detect, by surface plasmon resonance imaging, anti-Delta genotype 1, 6, 8 specific antibodies among Hepatitis D Virus infected patients.…”
Section: Biomimeticsmentioning
confidence: 90%
“…L'analyse en microscopie électronique de la RNP d'HDV révèle une structure sphérique d'environ 19 nm de diamètre. Le signal de localisation nucléaire (ou NLS) de S-HDAg, accessible à la surface de la RNP [14,15], permet la translocation de la protéine vers le noyau. On ne sait si L-HDAg est encore présente dans la RNP lors de la transcription des différents ARN d'HDV.…”
Section: La Ribonucléoprotéine D'hdvunclassified
“…Elles présentent donc une activité d'autoclivage qui hydrolyse les ARN linéaires néo-synthétisés en monomères, qui sont eux-mêmes circularisés de façon covalente, probablement par une ligase cellulaire. Un seul gène porté par l'ARN HDV de polarité antigénomique code les deux isoformes de la protéine qui sont successivement synthétisées pendant le cycle viral : non ramifiée qui associe des régions parfaitement bicaténaires à de petites protubérances et des boucles internes, lui conférant une configuration flexible [14].…”
Section: Le Génome De L'hdv Dans Sa Ribonucléoprotéineunclassified